Effectiveness of Non-Invasive Physiotherapy in Optimising Mucus Drainage and Sinus Ventilation in Sinusitis: A Literature Review - -, Luh Putu Surya Sintia Dewi; Anak Agung Istri Trisia Anggunningrat; Duri Ray Rikardus Rengga; Ni Nyoman Ryanti Wijayani (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Sinusitis is an inflammatory condition of the paranasal sinuses that can cause pain, pressure, and swelling. From the many symptoms that can arise due to sinusitis, physiotherapy can reduce dependence on pharmacological interventions and minimise long-term side effects. The purpose of this study was to determine the effectiveness of non-invasive physiotherapy in optimising mucus drainage and sinus ventilation in sinusitis patients. Methods: conducted was a literature review. The author conducted a comprehensive exploration on various academic databases that can be accessed online, including Google Scholar, PubMed, PEDRO, and Scopus. The keywords used in the search were "Physiotherapy, Intervention, Manual Therapy, Modalities Therapy, Sinusitis". The article selection process used PRISMA flow. Results: The results showed significant differences in various clinical parameters with a p-value range between p < 0.001 to p = 0.039, where ultrasound therapy and LLLT provided more rapid improvement, while breathing exercises and manual techniques had long-term effects for impaired mucus drainage and ventilation. Conclusion: Physiotherapy Interventions that can be given in cases of sinusitis, namely therapies such as ultrasound modalities, shortwave diathermy, Low-Level Laser Therapy, manual sinus drainage, self sinus massage, Jade Stone Mobilisation and yoga postures have proven effective in reducing symptoms of chronic sinusitis, including pain, sinus obstruction, and inflammation